Estimates of the severity of coronavirus disease 2019: a model-based analysis - Verity, R; Okell, LC; Dorigatti, I; Winskill, P; Whittaker, C; Imai, N; Cuomo-Dannenburg, G; Thompson, H; Walker, PGT; Fu, H; Dighe, A; Griffin, JT; et al. (Elsevier, 2020)
Background: In the face of rapidly changing data, a range of case fatality ratio estimates for coronavirus disease 2019 (COVID-19) have been produced that differ substantially in magnitude. We aimed to provide robust estimates, accounting for censoring and ascertainment biases.